Effects of glycyrrhizinic acid on neuromotor function in leptin-resistant mice - T. M. Matuzok; V. A. Prikhodko; S. M. Napalkova; O. V. Buyuklinskaya; S. V. Okovityi (Разработка и регистрация лекарственных средств, 2023)
Introduction. Among all types, type 2 diabetes mellitus (T2DM) shows the most rapidly growing prevalence, and has the greatest number of complications including peripheral polyneuropathy, which is aggravated with age. In view of this, the search for effective agents for the correction of T2DM-associated polyneuropathy is highly relevant.Aim. To study the effects of course administration (1 month) of glycyrrhizinic acid (GA) (20 mg/kg/d) on neuromotor function in female leptin-resistant diabetic db/db mice of different ages using stimulation electroneuromyography (ENMG).Materials and methods. The study was conducted in female C57Bl/Ks-db+/+m (db/db) mice weighing 40–48 g, aged 2 months (n = 15) or 6 months (n = 10) that were randomized into 4 groups: 1) control (C) (2 months (C2): n = 7; 6 months (C6): n = 5); 2) GA-treated (20 mg/kg/d p/o × 1 month) (2 months (GA2): n = 8; 6 months (GA6): n = 5). Following 1 month of treatment, an ENMG study of m. gastrocnemius and m. biceps brachii electrical activity was conducted using the following protocols: single stimulus presentation, electrical stimulation-induced fatigue, and repetitive stimulation. Additionally, nerve conduction velocity (NCV) was measured for n. ischiadicus.Results and discussion. In the GA2 group, compound muscle action potential (CMAP) peak amplitude and area in the biceps were 37.4 % (p < 0.05) and 44.5 % (p < 0.01) lower than respective control values, which may be related to possible hypokalemia induced by long-term GA use, including that resulting from 11β-hydroxysteroid dehydrogenase-2 inhibition. The relatively smaller reduction of the same parameters observed in the GA6 group may be explained by lower basal enzyme activity in aged animals. CMAP durations in the biceps were 21.7 % lower in the C6 group vs. C2 (p < 0.05), while threshold current values were 48.4 and 50.4 % higher in both GA2 and C6 groups vs. C2 (p < 0.01 for both). The decrease in CMAP duration and increase in threshold currents possibly reflects age-associated changes including muscle fiber and motor unit loss.Conclusion. GA (20 mg/kg/day × 1 months) in young adult (2 months) female leptin-resistant mice reduced single stimulus-induced CMAP amplitude and area in the biceps muscle. The compound had no effect on sciatic NCV and post-ESIF recovery rates of the gastrocnemius and biceps in both 2 month- and 6 month-old mice.